Tech-X DSTA challenge vision-360 indoor cognitive navigator - Antonius, Tio Favian (2009)
The purpose of this project is to design and implement a strategy to visually recognize corridors and plan paths for building a tree-based map. This project is a continuation of the previous final year project about robot localization. Through experiments, various image processing techniques such as polar transform, color image segmentation, image histogram equalization, image erosion, etc has been reviewed. The final purpose of reviewing those techniques is to provide best images as an input to enable the module to correctly identify corridors and navigate the robot towards it.